2017
DOI: 10.1016/j.gaitpost.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Minimum number of days required for a reliable estimate of daily step count and energy expenditure, in people with MS who walk unaided

Abstract: A minimum of 2days for step count and 4days for EE, regardless of day type, is needed to reliably estimate daily step count and daily EE, in people with MS who walk unaided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
6
11
0
Order By: Relevance
“…First, averaging 2 days of step counts provides an adequate level of reliability (≥0.7), which approximates a very high level of reliability estimates when averaging data for an entire week (0.9). This was replicated by Norris et al [23], who reported similar findings using an approach that examined reliability coefficients from random 2-day to 7-day averages. In addition, obtaining a stable measure of freeliving walking activity based on pedometer use may require 7 days in healthy individuals [33], while more impaired populations such as incomplete spinal cord injury patients may require only 2 days of monitoring to achieve acceptably stable estimates [34].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…First, averaging 2 days of step counts provides an adequate level of reliability (≥0.7), which approximates a very high level of reliability estimates when averaging data for an entire week (0.9). This was replicated by Norris et al [23], who reported similar findings using an approach that examined reliability coefficients from random 2-day to 7-day averages. In addition, obtaining a stable measure of freeliving walking activity based on pedometer use may require 7 days in healthy individuals [33], while more impaired populations such as incomplete spinal cord injury patients may require only 2 days of monitoring to achieve acceptably stable estimates [34].…”
Section: Discussionsupporting
confidence: 53%
“…There is a continued need for more evidence of usage in realworld settings; larger samples, broader functional ranges, and appropriate metrics to gain greater confidence in the use of activity monitors in tracking and managing MS. For example, Norris et al [23] found that to calculate a reliable mean daily step count in unaided walking, a minimum of any random 2-day combination is required. However, that study was conducted with a relatively small sample of MS patients that were not highly functioning.…”
Section: Introductionmentioning
confidence: 99%
“…For the present analyses we used only participants who provided 4 days of valid daily EE data (n = 62), because preliminary analysis using the generalizability theory indicates that a minimum of any 4 days of the week provides a reliable estimate of average daily EE. 29 The SenseWear Armband Social cognitive theory is one of the most widely adopted theoretical frameworks for understanding and optimizing PA behavior. It is characterized by four constructs: self-efficacy, outcome expectations, goal setting, and barriers and facilitators.…”
Section: Pa Measurementioning
confidence: 99%
“…Compared with measures from a portable metabolic system (i.e., Oxycon Mobile), the SWA overestimated METs by 15.4% for individuals using at most a stick to walk and 6.6% for those needing bilateral support [77]. For reliably estimating physical activity in MS using the SWA, a study by Norris et al [78] provides indication that at least 2 and 4 days of monitoring are required for reliable estimates of steps and energy expenditure in fully ambulatory persons with MS.…”
Section: Research From 2013–2017: What Is New?mentioning
confidence: 99%